Treatment of turbid surface water using Oppuntia ficus-indica as a plant-based coagulant : Research article - Megersa, Moa (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2024)
Researchers are looking for sustainable alternatives to address current issues related to water quality because developing countries often lack access to suitable water treatment technologies and pose health dangers in both rural and urban areas. Plant species have shown promising results for use in turbid water treatment. In this context, Opuntia ficus-indica was tested for its ability to reduce the turbidity of surface water and synthetic kaolinite suspensions. The field and experimental research was carried out was conducted from February 2021 to March 2022. Coagulation tests were performed as part of the experimental investigation in the Laboratory of the Biology Department of Madda Walabu University. Total dissolved solids, electrical conductivity, temperature, turbidity, and pH were measured for water physicochemical examination according to the protocol. Doses ranging from 10 mg/L to 50 mg/L were used to investigate how the dose affects the reduction in turbidity. The impact of initial turbidity on the effectiveness of coagulation was studied using surface (33 ntu) and synthetic water (60 and 100 ntu) samples. All experiments were conducted in duplicate and the means were calculated. According to the study findings, O. ficus-indica reduced turbidity to 5ntu at the optimal dose of 20 mg / L in 33 ntu, 40 mg / L in 60 ntu and 100 ntu using 0.5 NaCl as a solvent. The efficiency of O. ficus indica removal in turbid river water was 85%. Using synthetic turbid water, O. ficus-indica extracts showed 91.6% turbidity removal efficiency at 60 ntu, whereas at 100 ntu, the extracts showed 95% turbidity removal efficiency. At pH 8, O. ficus-indica performed best (87% turbidity removal efficiency). The pH of the river water samples was only minimally altered by coagulation with extracts of O. ficus-indica. The same river water that was treated with alum had a pH that was reduced from 6.5 to 3.45, making the water acidic. According to the results of the present study, O. ficus indica is a viable substitute for turbid surface water because it effectively eliminates turbidity. By guaranteeing water availability and sustainable management, this species can be crucial to achieving one of the Sustainable Development Goals.